An Exploration of Clinical Learning Experiences of Higher Diploma Nursing Students at Kenyatta National Hospital, Kenya. - Kipsoi, Mary Jebichii (Amref International University, 2025)
Background: Clinical learning experiences, defined as active student engagement in direct patient care under the supervision of experienced educators, are essential for developing nursing competency and confidence. However, many nursing students face difficulties translating theoretical knowledge into practice, particularly in high-pressure hospital settings. An internal review at Kenyatta National Hospital (KNH), a major referral facility in Kenya, revealed that several Higher Diploma nursing students felt inadequately prepared for clinical assessments and struggled with hands-on skills. Objective: This study aimed to explore the clinical learning experiences of Higher Diploma nursing students at KNH, focusing on factors influencing their clinical engagement and preparedness. Method: A qualitative descriptive approach was used. Data were collected through in-depth interviews (n=12) and two focus group discussions (n=12) involving purposively sampled Higher Diploma nursing students. A semi-structured interview guide facilitated data collection. Thematic analysis was conducted using Braun and Clarke’s six-step framework, with attention to trustworthiness principles such as credibility and confirmability. Results: Three major themes emerged: First, personal challenges and triumphs, including work-life balance, health, and financial constraints; secondly, systemic support structures, such as mentorship, peer learning, policy gaps, and access to resources; and thirdly a holistic clinical learning environment, encompassing space adequacy, emotional safety, and coping with stressors. These factors collectively influenced students’ engagement and learning outcomes during clinical placements Conclusion and Recommendations: The clinical learning experiences of higher diploma nursing students at Kenyatta National Hospital are influenced by personal, institutional, and environmental factors. Students’ work-life balance, health, and financial stability impact their effectiveness in clinical learning. Equally important are effective mentorship, peer learning, clear policies, and access to functional resources. A safe, well-equipped, and supportive clinical environment promotes emotional resilience. The findings highlight the need for targeted strategies to improve the clinical learning experiences. Future research should include longitudinal studies to explore how students’ physical and mental health relates to their clinical learning experiences.
A Research Thesis Submitted in Partial Fulfillment for the Degree of Master of Science in Health Professions Education, Department Of Health Systems Management, School of Public Health of The Amref International University
Keywords: Clinical Learning Experiences